1911 Tenn. Priv. Acts 1431, A Bill to Be Entitled "An Act to Amend the Charter of the City of Knoxville, Tenn. . . . ," ch. 498, § 45. - (:unkn) unknown (My University, 1911)
That no officer of Election or Commissioner of Election shall be in, at, or near any ballot box or voting precinct during any election or the canvassing of the returns armed with pistol, gun, or other deadly weapon[.]
Keywords: PEACE OFFICERS